Investigação da modelagem da informação da cidade como ferramenta de gestão de indicadores de sustentabilidade urbana - Garcia, Guilherme Augusto Palmeira (2022)
This research is instigated by the search for sustainability in processes, especially on urban spaces. Furthermore, there is a gradual increase in importance of the roles played by cities on a global scale. Therefore, there is a need to expand and improve urban planning and management. Considering this, the management of existing urban sustainability indicators is analyzed through City Information Modeling (CIM), as an approach that integrates the fields of urbanism, engineering, and computer science. To apply said analysis, it was collected from different sources 858 indicators as well as technologies and researches in CIM. Then, using their crossed features, a SWOT analysis was carried out to obtain the positive and negative aspects inherent of the management process, as well as opportunities and threats that the application is subject to by the external environment. With the results of this analysis, it is inferred that the application of CIM in the management of indicators is effective, especially in visualization, data collection and generation of scenarios, contributing to decision making. However, it is limited to physical issues or urban infrastructure and to the systematic collection and quality of data. It is also concluded that it presents itself as a means of promoting public participation and environmental education. Finally, the establishment of urban sustainability indicators is linked to the change of paradigms in the current way of urban management. Knowing this, the present work is a contribution on this topic precisely, pointing out the potential of the joint use of CIM and sustainability indicators for a more sustainable city and pointing to paths that can be traced in future research.